2008
DOI: 10.1016/j.molcel.2008.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90-Dependent Activation of Protein Kinases Is Regulated by Chaperone-Targeted Dephosphorylation of Cdc37

Abstract: SummaryActivation of protein kinase clients by the Hsp90 system is mediated by the cochaperone protein Cdc37. Cdc37 requires phosphorylation at Ser13, but little is known about the regulation of this essential posttranslational modification. We show that Ser13 of uncomplexed Cdc37 is phosphorylated in vivo, as well as in binary complex with a kinase (C-K), or in ternary complex with Hsp90 and kinase (H-C-K). Whereas pSer13-Cdc37 in the H-C-K complex is resistant to nonspecific phosphatases, it is efficiently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
178
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(187 citation statements)
references
References 46 publications
6
178
2
1
Order By: Relevance
“…These mutations also impair PP5's ability to dephosphorylate phospho-GR-Ser211, another known target of PP5 discussed in detail later (2). These data are in agreement with our previous work, in which overexpression of PP5 in HCT116 colon cancer cells enhanced Cdc37 dephosphorylation (8).…”
Section: -23)supporting
confidence: 92%
See 3 more Smart Citations
“…These mutations also impair PP5's ability to dephosphorylate phospho-GR-Ser211, another known target of PP5 discussed in detail later (2). These data are in agreement with our previous work, in which overexpression of PP5 in HCT116 colon cancer cells enhanced Cdc37 dephosphorylation (8).…”
Section: -23)supporting
confidence: 92%
“…Dysregulation of this step by overexpression of PP5 with concomitant reduction in phospho-Cdc37-Ser13 results in reduced Raf-1 activity in HCT116 cells. In yeast, both the overexpression and deletion of the ortholog, Ppt1, causes reduced v-Src activity (8). To understand how Cdc37 dephosphorylation affects the activation mechanism of Hsp90-dependent kinases, we investigated the impact of PP5 mutants on chaperoning of the kinase clients Cdk4 and Raf-1.…”
Section: -23)mentioning
confidence: 99%
See 2 more Smart Citations
“…1D). However, in vivo experiments had suggested that phosphorylation of Cdc37 is involved in regulating its function (19,36). When we used a Cdc37 variant in which the phosphorylation was mimicked by a glutamate substitution (Cdc37 E ), also this variant alone had no significant influence on v-Src (Fig.…”
Section: Significancementioning
confidence: 97%